Honey - Banta, Isabel (Celadon Books, 2024)
"An addictive coming-of-age story that follows the meteoric rise of pop star Amber Young as she navigates fame and self-discovery in the late 90s and early 2000s It is 1997, and Amber Young has received a life-changing call. It's a chance thousands of girls would die for: the opportunity to join girl group Cloud9 in Los Angeles and escape her small town. She quickly finds herself in the orbits of fellow rising stars Gwen Morris, a driven singer-dancer, and Wes Kingston, a member of the biggest boy band in the world, ETA. Surrounded by people who claim to love her but only wish to exploit her, Amber's rich interior life is frequently reduced. Before she even knows who she is, the men surrounding her have decided what she's capable of. Driven by a desire for recognition and success, for love and sex, for agency and connection, Amber comes of age at a time when the kaleidoscope of public opinion can distort everything and one mistake can shatter a career. With the captivating style of Sweetbitter by Stephanie Danler and the raw honesty of I'm Glad My Mom Died by Jennette McCurdy, Isabel Banta's debut novel, Honey, redefines the narratives of some of the most famous pop icons of the 90s and 2000s. It reimagines the superstars we idolized and hated, oversexualized and underestimated, and gives them the fresh, multifaceted story they deserve"--